How do subsidiaries assume autonomy? A refined application of agency theory within the subsidiary‐headquarters context. (10th February 2017) - Cavanagh, Andrew; Freeman, Susan; Kalfadellis, Paul; Cavusgil, Salih Tamer
Abstract : Research Summary: While the notion of subsidiary autonomy has received considerable attention within the international business literature, extant research is yet to comprehensively distinguish between the different types of subsidiary autonomy. This article outlines a key type that is independently claimed by the subsidiary, 'assumed autonomy, ' and makes the following contributions: first, we outline the causes for this type of autonomy. Second, we elucidate how assumed autonomy is viewed by the head office. In doing so, the article also challenges previous applications of agency theory within the subsidiary‐headquarters context, arguing the need for a refined, more nuanced interpretation in this setting to reflect a revised set of agency theory assumptions. Managerial summary: Despite representing a key issue in subsidiary management today, the types of autonomy that may be acquired by, or available to, a subsidiary are not yet fully understood. This article aims to reduce the confusion in this respect by outlining a key type of autonomy that is 'assumed' by the subsidiary without explicit delegation from the head office. We explain the reasons why this type of autonomy may be developed by the subsidiary and also how it is likely to be viewed by the head office. We anticipate that this will in turn have significant implications for the ongoing viability and value of the subsidiary within the multinational, and it highlights the importance of head office managers adopting a more open‐minded approach to proactive subsidiary behavior. Copyright © 2016 Strategic Management Society.